Finite Element Analysis of the Influence that Bone Density and Implant Fixation Features have on Total Ankle Tibial Component Stability - Joshua E. Johnson PhD; Gabriel Clarke MS; Cesar de Cesar Netto MD, PhD; Bopha Chrea MD; Donald D. Anderson PhD (Foot & Ankle Orthopaedics)
Background: Primary implant stability is important for successful outcomes after uncemented total ankle replacement (TAR). However, the influence of patient-specific bone density on TAR performance is poorly understood, especially for implants that rely on press-fit for stable primary fixation. Our goal was to evaluate how bone density influences implant-bone interfacial micromotions in 3 press-fit tibial component designs by sampling from a TAR preoperative planning database using finite element analysis (FEA). Methods: FEA was conducted in 4 TAR patients with relatively low-density (n = 2, lowest 10% of a sample including 58 patients) and average-density (n = 2, midrange of sample) bone as assessed from deidentified patient CT scans. Three tibial implant designs were evaluated: a bone-sparing resurfacing implant, a cortex-sparing anterior approach monoblock stemmed implant, and a distal-reaming modular stemmed implant. Implants were inserted into tibia geometries obtained from the CT scans. Press-fit implantation was modeled first, followed by loadings from the stance phase of gait, and the associated micromotions were computed from the FEA output. Results: In general, patients with average-density bone had FEA predicted lower micromotions than patients with low-density bone. FEA suggests that implant fixation features had less influence on micromotions in patients with average-density bone, with peak micromotions ranging from 2 to 23 µm (3.1 ± 1.3 µm average micromotion). For patients with low-density bone, interfacial regions are predicted to experience micromotions exceeding the bony ingrowth threshold of 50 µm only for the resurfacing implant. Conclusion: We investigated the influence of bone density on implant-bone micromotions with varying primary fixation features using FEA. The model predicts that micromotions are less in average-density bone, regardless of implant fixation features. However, both stemmed devices showed lower micromotions in less-dense bone, albeit with the corresponding clinical trade-off of requiring more tibial bone removal. Clinical Relevance: The results presented here implicate the complementary role that local bone density plays in the primary fixation stability of uncemented TAR.